Active Aging Index in Vietnam Relative to China, South Korea, Taiwan, and 28 European Union Countries. (October 2020) - Pham, Tuan-Vu; Hsu, Hui-Chuan; Zaidi, Asghar; Chen, Ya-Mei
Objectives: This study constructed an Active Aging Index (AAI) for Vietnam and compares Vietnam's AAI with those of China, Korea, Taiwan, and 28 countries in the European Union. Methods: A survey of 1, 105 people aged 55 or above in three provinces from the northern, central, and southern parts of Vietnam was conducted. Active aging was measured using the AAI; its 22 indicators were grouped into four domains: employment, social participation, independent/healthy/secure living, and enabling environments. Results: Of the 32 countries reviewed, Vietnam ranked 11th. It ranked high for employment (1st) and social participation (5th) but low for independent/healthy/secure living (32nd) and enabling environments (26th). Conclusion: Three policy priorities were identified: maintaining a high preference-driven social and workforce participation rate among older adults; promoting medical care and healthy behaviors among older adults; and improving other poorly performing aspects of active aging, including voluntary activities, poverty risk, Internet usage, and lifelong learning.